May family routines impact oral health in American children? - Pardi, Vanessa; Castilho, Giovanna Torqueto [UNESP]; Stewart, Rachel; Luo, Huabin; Wright, Wanda G.; Moss, Mark Eric (My University, 2024)
Objectives: The present study aimed to assess the association between family routines and dental caries and self-rated oral health status. Methods: Data from the 2020–2021 National Survey of Children's Health (NSCH) completed at United States were used. Our outcome variables were self-reported dental caries (yes/no) and poor oral health condition (yes/no). Our independent variables were related to family routines: (1) Going to bed at the same time (yes/no); (2) Days having dinner together (0–7days); (3) Hours spent in front of the TV, computer, cell phone or other electronic devices (screen time); and (4) adequate sleep (yes/no). We used socioeconomic factors, health insurance coverage, family structure and neighborhood characteristics as covariates. Univariate and multiple logistic regression were used to analyze the data. Results: For the dental caries outcome, children with regular bedtimes (AOR = 0.68, 95% CI: 0.58–0.79), more frequent family dinners (AOR = 0.90, 95% CI: 0.85–0.96), and supportive neighborhoods (AOR = 0.88, 95% CI: 0.78–0.99) were less likely to report dental caries. Increased screen time (AOR = 1.10, 95% CI: 1.04–1.15) was associated with higher self-reported dental caries. For oral health status, children with regular bedtimes, (AOR = 0.60, 95% CI: 0.48–0.75), supportive neighborhoods (AOR = 0.81, 95% CI: 0.68–0.97), and with more neighborhood amenities (AOR = 0.92, 95% CI: 0.88–1.00) reported better health. More screen time (AOR = 1.11, 95% CI: 1.02–1.21) and poor neighborhood conditions (AOR = 1.13, 95% CI: 1.02–1.26) correlated with poor oral health. Conclusions: Findings from this study indicate that family routines play a significant role in children's oral health. Future research should focus on interdisciplinary family- and community-level interventions that are tailored to support healthy habits and address the needs of families.
Keywords: bedtime; dental caries; family; mealtime; neighborhood characteristics; oral health; screen time; sleep